MINERAL RESOURSE OF UZBEKISTAN AND THEIR GLOBAL IMPORTANCE. COTTON INDUSTRY:HISTORY AND CURRENT ROLE IN THE ECONOMY - Teshaboyeva Nafisa Zubaydulla qizi; Igor Chekulay Vladimirovich; Soibjonova Bahora (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this article discusses the mineral resources of Uzbekistan and their significant global importance, as well as the country’s cotton industry and its current role in the national economy. It explains how Uzbekistan has developed its rich mineral base—including gold, copper, uranium, and other valuable metals—and how these resources contribute to both domestic economic growth and international trade. The article highlights the strategic importance of Uzbekistan’s minerals, which are used in energy production, industry, and technology, making the country an important player in global markets.It also emphasizes the role of the cotton industry, which has historically been one of Uzbekistan’s key agricultural sectors. Cotton production continues to support the rural economy, provide employment, and contribute to export revenues. The article outlines modern reforms and innovations in the cotton sector, including the introduction of environmentally friendly farming practices, mechanization, and digital technologies to increase productivity and quality.Furthermore, the article describes efforts to diversify the economy by linking the mineral and cotton industries to broader industrial and manufacturing development. These initiatives have strengthened Uzbekistan’s economic resilience, improved living standards, and expanded its participation in international trade.Overall, the article shows how Uzbekistan’s natural resources and strategic industries—through careful management, modernization, and international cooperation—play a vital role in building a strong, competitive, and sustainable economy that successfully balances traditional strengths with modern growth.